Precision Medicine in Inflammatory Bowel Diseases - Marafini, Irene; Monteleone, Giovanni (Frontiers in Pharmacology, 2021)
In the last decades, a better understanding of the molecular mechanisms sustaining the pathogenic process in inflammatory bowel diseases (IBD) has contributed to expand the therapeutic armamentarium for patients with these disorders. Alongside with traditional therapies, monoclonal antibodies against tumor necrosis factor-α, the interleukin (IL)-12/IL-23 p40 subunit and the α4β7 integrin, and tofacitinib, a small molecule inhibiting intracellular pathways downstream to cytokine receptors, have entered into the clinic. However, not all IBD patients respond to or tolerate these drugs and some of the responders lose response over time. Such a therapeutic failure is, at least in part, dependent on the fact that IBD-associated tissue damage is driven by simultaneous activation of multiple and distinct immune-inflammatory signals and the detrimental mucosal immune response changes over time even in the same patient. Therefore, personalized approaches aimed at identifying which patient should be treated with a specific drug at a precise time point are worth pursuing. A such approach has the advantage to improve efficacy of the drug and limit adverse reactions, thereby improving quality of the life of the patients and reducing costs. In this review, we summarize all the available evidence about the possible role of precision medicine in IBD.